2006
DOI: 10.1159/000091160
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Radiotherapy (IORT) as a Boost in Patients with Early-Stage Breast Cancer – Acute Toxicity

Abstract: Background: We report on acute toxicities as well as the early cosmetic outcome of patients receiving intraoperative radiotherapy (IORT) followed by whole-breast radiotherapy (WBRT) compared to patients treated with standard WBRT alone. Patients and Methods: From 2/2002 until 2/2005, 84 breast cancer patients were treated with IORT during breast-conserving surgery (BCS) as a boost (20 Gy/50 kV X-rays) followed by WBRT. After wound healing, all IORT patients were treated with WBRT at a total dose of 46 Gy. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 31 publications
1
41
1
2
Order By: Relevance
“…The clinicopathological rationale, the technology of the device, surgical technique (fi gure 1), radiobiology, and acute and long-term toxicity have been previously described. 5,[14][15][16][17][18][19][20][21][22][23][24] Briefl y, the Intrabeam device provides a point source of low energy x-rays (50 kV maximum) at the tip of a 3·2 mm diameter tube that is placed at the centre of a spherical tumour bed applicator. After surgically positioning the appropriately sized applicator in the tumour bed, radiation is switched on for 20-35 min to target the tissues that are at highest risk of local recurrence.…”
Section: Methodsmentioning
confidence: 99%
“…The clinicopathological rationale, the technology of the device, surgical technique (fi gure 1), radiobiology, and acute and long-term toxicity have been previously described. 5,[14][15][16][17][18][19][20][21][22][23][24] Briefl y, the Intrabeam device provides a point source of low energy x-rays (50 kV maximum) at the tip of a 3·2 mm diameter tube that is placed at the centre of a spherical tumour bed applicator. After surgically positioning the appropriately sized applicator in the tumour bed, radiation is switched on for 20-35 min to target the tissues that are at highest risk of local recurrence.…”
Section: Methodsmentioning
confidence: 99%
“…We had also ascertained that the combination of TARGIT and EBRT is safe, as tested in a 25-patient pilot study in UCL, London. 22,27 In fact, giving TARGIT at the time of surgery as a tumour bed boost followed by subsequent EBRT has been found to result in a very low 5-year recurrence rate of 1.73%, 27,28 with favourable toxicity and cosmetic outcome results; [29][30][31][32] furthermore, mathematical models of TARGIT have recently suggested that it could be superior in terms of local control to conventional radiotherapy. 33,34 This could be because of the radiotherapy limiting breast cancer cell proliferation normally caused by the trauma of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical complications are reported at similar rates in series in the literature (5-8%). Kraus et al (17) reported the potential problems in the first months as hematoma, cellulitis, and fat necrosis, while late complications after 1 year are reported to be due to radiation (5,16).…”
Section: Discussionmentioning
confidence: 99%